203 SPONTANEOUS REGRESSION OF INFLAMMATORY PSEUDOTUMOR OF THE BLADDER IN A CHILD. (1st January 2005) - Fletcher, S. G.; Galgano, M.; Michalsky, M. P.; Roth, J. A.
Abstract : Inflammatory pseudotumor of the bladder is a benign proliferative lesion of the submucosal stroma which cannot be distinguished endoscopically or radiographically from malignant tumors of the bladder (e.g. transitional cell carcinoma or rhabdomyosarcoma. The case presented here is the first, to our knowledge, of an inflammatory pseudotumor of the bladder treated with conservative management in a child. A previously healthy 6-year-old male presented to his PCP with a three week history of intermittent lower abdominal pain, constipation, mild dysuria and a physical examination remarkable for a palpable suprapubic mass. UA and KUB were unremarkable. CT scan and cystoscopy revealed a suspicious mass arising from the posterior aspect of the bladder. Transurethral resection (TUR) of the bladder tumor was performed. Frozen-section analysis from several TUR as well as open biopsy specimens showed no evidence of malignancy. No further surgical resection was performed. The final pathology demonstrated inflammatory pseudotumor. The patient was further treated with a two-week course of Augmentin and ibuprofen. Re-evaluation approximately six weeks later (abdominal and pelvic CT scan and cystoscopy) revealed no evidence of residual tumor. There are many reports in the literature of locally aggressive pseudotumors in organ systems other than the GU tract, and a few describe progression to malignant behavior. This has prompted some to recommend open surgery with partial cystectomy for bladder preservation in the case of bladder involvement with children. Others have advocated complete local excision via transurethral resection. With proper diagnostic rigor and close follow-up, pediatric cases may be treated successfully with nonsurgical therapy alone.